The Role of Akt in Acquired Cetuximab Resistant Head and Neck Squamous Cell Carcinoma: An In Vitro Study on a Novel Combination Strategy - Zaryouh, Hannah; De Pauw, Ines; Baysal, Hasan; Pauwels, Patrick; Peeters, Marc; Vermorken, Jan Baptist; Lardon, Filip; Wouters, An (Frontiers in Oncology, 2021)
The epidermal growth factor receptor (EGFR) is a therapeutic target in head and neck squamous cell carcinoma (HNSCC). Resistance to EGFR-targeted therapies, such as cetuximab, poses a challenging problem. This study aims to characterize acquired cetuximab resistance mechanisms in HNSCC cell lines by protein phosphorylation profiling. Through this, promising combination treatments can be identified to possibly overcome acquired cetuximab resistance in HNSCC. Protein-phosphorylation profiling showed increased phosphorylation of Akt1/2/3 after cetuximab treatment in acquired cetuximab resistant cells compared to cetuximab sensitive cells, which was confirmed by western blotting. Based on this protein phosphorylation profile, a novel combination treatment with cetuximab and the Akt1/2/3 inhibitor MK2206 was designed. Synergy between cetuximab and MK2206 was observed in two cetuximab sensitive HNSCC cell lines and one acquired cetuximab resistant variants in simultaneous treatment schedules. In conclusion, this study demonstrates that increased Akt1/2/3 phosphorylation seems to be characteristic for acquired cetuximab resistance in HNSCC cell lines. Our results also show an additive to synergistic interaction between cetuximab and MK2206 in simultaneous treatment schedules. These data support the hypothesis that the combination of cetuximab with PI3K/Akt pathway inhibition might be a promising novel therapeutic strategy to overcome acquired cetuximab resistance in HNSCC patients.